Pest categorisation of Coleosporium phellodendri. (15th November 2022) - ,; Bragard, Claude; Baptista, Paula; Chatzivassiliou, Elisavet; Di Serio, Francesco; Gonthier, Paolo; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; et al.
Abstract: The EFSA Plant Health Panel performed a pest categorisation of Coleosporium phellodendri Kom., a basidiomycete fungus belonging to the order Pucciniales, causing rust diseases on Pinus spp. (aecial host) and on Phellodendron spp. (telial host). C. phellodendri has been reported only from Asia (namely, China, Republic of Korea, Japan and Russia) and is not known to be present in the EU territory. The pathogen is not listed in Annex II of Commission Implementing Regulation (EU) 2019/2072, an implementing act of Regulation (EU) 2016/2031, or in any emergency plant health legislation. The pathogen could enter into, become established in, and spread within the EU territory via host plants for planting and host plant parts (e.g. foliage, branches) other than seeds and fruits, respectively. Spread within the EU territory may also occur by natural means if Phellodendron spp. were present. Availability of the Pinus spp. and climate suitability factors occurring in the EU are favourable for the establishment of the pathogen in areas where Phellodendron spp. are also present. Phytosanitary measures are available to prevent the introduction and spread of the pathogen in the EU. C. phellodendri does not satisfy all the criteria assessed by EFSA for consideration as a Union quarantine pest as no economic and environmental impact of this pathogen is expected without widespread presence of Phellodendron spp. in the EU.